Identification of COVID-19-associated myocarditis by speckle-tracking transesophageal echocardiography in critical care - Wehit, Jeanette M. (2020)
A 68-year-old male presented with flu-like symptoms, fatigue, history of obesity, hypertension, type 2 diabetes and chronic smoking. Chest radiography revealed right basal opacity consisting of infiltrate. With respiratory failure, orotracheal intubation and mechanical ventilation were performed. Patient presented gas exchange alteration. Real-time PCR detected SARS-CoV-2. Treatment with liponavir/ritonavir and hydroxychloroquine was started. Because of poor acoustic window, speckle-tracking transoesophageal echocardiography (TEE) was performed, detecting deterioration in global longitudinal strain. Acute COVID 19 infection led us to suspect myocarditis, with no other signs or symptoms other than elevated troponin and altered strain. On day 15, the patient suffered bacteraemic sepsis at endovascular focus with Serratia marcescens and multiorgan failure. TEE-guided haemodynamic monitoring was repeated showing global longitudinal strain improvement. Acute COVID 19 infection led us to suspect myocarditis, with no other signs or symptoms beyond elevated troponin and altered strain.